(3GdGOGQI HGdQbGHIs - (3eMeO YjSi(B, (3GdaGYhQjs ((3YeGf(B:s (3OGQ GdcfhR GdeYQaI(B,s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3eaghe GdQbGHI GdEOGQjI h YfGUQgG h GgejJgG h CgOGagG, CfhGY GdQbGHI,YedjI GdQbGHI aj GdEOGQI, CSGdjH GdQbGHI aj GdEOGQI GdYGeI, CLgRI GdQbGHI GdOGNdjI hhMOGJ GdQbGHI GdOGNdjI h OjhGf GdNOeI GdeOfjI aj GdCQOf, GdaSGO GdEOGQj h OhQ GdMcheI aj GdMO efg aj GdCQOf,eHOG TQYjI GdQbGHI, GdQbGHI h GdeSDhdjI hCNdGbjGJ GdhXjaI GdYGeI, YdGL eTcdI GdeSDhdjI h GdeSGAdI h GdQbGHI , GdQbGHI Ydi GdeDSSGJ GdYGeI, OhQ GdeYdheGJ aj GdQbGHI GdEOGQjI, eaghe GddGeQcRjI aj GdEOGQI GdJQHhjI, GdEUdGMGJ GdEOGQjI aj GdCee GdeJMOIf GdaSGO gd jJbdU Ce jROGO aj GdhWf GdYQHj, JTQjYGJ GdUMGaI GdYQHjI Hjf KbGaI Mbhb GdEfSGf h KhQI GdEJUGdGJ GdOhdjI(B. s
(3HjHdjhZQGajG U(B. 283s
Keywords: (3GOGQI GdGYeGds; (3GOGQI eTGQjYs